Liver Histopathological Analysis of 24 Postmortem Findings of Patients With COVID-19 in China - Chu, Huikuan; Peng, Li; Hu, Lilin; Zhu, Yixin; Zhao, Jinfang; Su, Hua; Yao, Lin; Zhu, Qingjing; Nie, Xiu; Yang, Ling; Hou, Xiaohua (Frontiers in Medicine, 2021)
Although the pathologic investigation of liver injury was observed in a couple of cases in China, the detailed description of liver histopathologic and ultrastructural changes in a relatively larger series of liver tissues from COVID-19 patients is lacking. Samples from the liver were obtained from 24 COVID-19 cases from February 1 to April 1, 2020. Light microscopy showed that all liver sections had different degrees of liver injury manifested as swelling of the hepatocytes, hepatocellular necrosis, steatosis, lobular inflammation, portal inflammation, dilatation of sinusoids, and so on. SARS-CoV-2 induced liver injury might be independent of pre-existing Schistosoma infection or obstructive cholestasis. Patients combined with respiratory failure had more severe hepatocellular necrosis and male patients were more susceptible to liver injury. Although coronavirus particles or viral inclusions were not detected in the liver tissues for all cases, vacuolar degenerations in hepatocytes, edematous of mitochondria with the disruption of cristae, and expansions of the endoplasmic reticulum were observed. In conclusion, pathologic changes of liver tissues provide us a further understanding of liver injury in COVID-19 patients. Changes in the liver seem to be related to the underlying diseases/conditions.